Non-performing loans, systemic risk and resilience in financial networks - Giulio Bottazzi; Alessandro de Sanctis; Fabio Vanni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
After the outbreak of the financial crisis in 2007-2008 the level of non-performing loans (NPLs) in the economy has generally increased. However, while in some countries this has been a transitory phenomenon, in others it still represents a major threat for economic recovery and financial stability. The present work investigates the relationship between non-performing loans and systemic risk using a network-based approach. In particular, we analyze how an increase in NPLs at firm level propagates to the financial system through the network of credits and debits. To this end we develop a model with two types of agents, banks and firms, linked one another in a two-layers structure by their reciprocal credits and debits. The model is analyzed via numerical simulations and allows a) to define a synthetic measure of systemic risk and b) to quantify the resilience of the financial system to external shocks, making it particularly useful from a policy point of view. For illustrative purposes, in section 3 we present an application of the model to Italy, Germany, and United Kingdom, using empirically observed data for the three countries.
Keywords: G21; C63; G01; D85; 330; financial crisis; network theory; non-performing loans; resilience; systemic risk